The Narrative of Crime in Andrea Hirata's Novel 'Orang-Orang Biasa': A Formulaic Study - Sari, Hanifah Yulia; Rachman, Aditya; Putri, Diantri Seprina; Ulya, Ridha Hasnul; Widhyah, Dhini Yustia (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2024)
The topic of criminality is often viewed as a literary genre closely associated with themes of crime, heroes and anti-heroes, mysterious plots, suspense, plot twists, and violent scenes. This study employs Andrea Hirata's novel